'He's got a life sentence, but I have a life sentence to cope with as well': the experiences of long-term prisoners' partners - Kotova, A (2016)
There is a small, but growing, body of research on prisoners' families. It has shown that these families experience numerous pains and deprivations associated with imprisonment, ranging from financial hardship to social (stigma) and emotional issues (grief-like emotions). It has also been suggested that long sentences could exacerbate and prolong these problems. However, no studies on long-term prisoners' families specifically have yet been conducted in the UK. This study explores the experiences of 33 long-term prisoners' partners. Prison sociology, which has explored imprisonment, and long-term imprisonment specifically, is used to inform the analysis. Themes such as coping with the pains of imprisonment over time and with the length of the sentence and time passing are explored. It is also shown that partners are fundamentally changed, on an identity level, by a long sentence. Furthermore, stigma is explored, and it is argued that partners of long-term prisoners experience especially strong stigma and that it lasts for a long time indeed. Finally, this thesis considers how the partners outside 'do family' across prison walls, and how imprisonment makes this challenging indeed. In conclusion, it is argued that the experiences of prisoners' partners speak to the sociological research on imprisonment more broadly and that drawing on these experiences can develop the prison sociologist's knowledge about the broader sociological impact of imprisonment.